2017
DOI: 10.1111/imm.12743
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 expression, haplotype and immune activation in protection from infection in HIV‐exposed uninfected individuals in HIV‐serodiscordant relationships

Abstract: Several host factors have been implicated in resistance to HIV infection in individuals who remain HIV-seronegative despite exposure. In a cohort of HIV-serodiscordant heterosexual couples, we investigated interactions between systemic inflammation and T-cell activation in resistance to HIV infection. Males and females in stable long-term relationships with either HIV-infected or uninfected partners were recruited, blood T-cell activation (CD38, HLA-DR, CCR5 and Ki67) and plasma cytokine concentrations were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 54 publications
1
14
0
1
Order By: Relevance
“…This mutation has been associated with increased CCR5 expression on CD4+ T cells and thus could explain the rapid progression to AIDS among the NCs. This mutation has been found to be associated with rapid progression in other studies (33)(34)(35). This mutation was significantly associated with disease acceleration, particularly an accelerated progression to death in Caucasians (16).…”
Section: Discussionmentioning
confidence: 66%
“…This mutation has been associated with increased CCR5 expression on CD4+ T cells and thus could explain the rapid progression to AIDS among the NCs. This mutation has been found to be associated with rapid progression in other studies (33)(34)(35). This mutation was significantly associated with disease acceleration, particularly an accelerated progression to death in Caucasians (16).…”
Section: Discussionmentioning
confidence: 66%
“…The authors concluded that the decreased frequencies of heterozygous CCR5∆32 in seropositive patients suggest partial resistance against HIV-1 infection thus affording protection [31]. In a South African-based study done by Jaumdally et al [33], the immune profiles of samples carrying protective and non-protective haplotypes were investigated. The authors investigated the interaction between systemic inflammation, immune activation of T-cells and CCR5 genotype in context to HIV-1 resistance.…”
Section: Acquired Immunodeficiency Syndromementioning
confidence: 99%
“…These individuals when grouped thus expressed protective CCR5 haplotypes and presented with reduced inflammatory cytokines. The data obtained by Jaumdally and co-workers [33] provides important biological information regarding samples presenting differential CCR5 status even before actual infection. The terms used to describe CCR5 (i.e., genotype, levels, haplotype, etc.)…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A dupla marcação de linfócitos com CD38+HLA-DR+ classicamente está associada com ativação e progressão da doença 52,53 . O receptor de membrana CCR5 está ligado à susceptibilidade à infecção pelo HIV, e também à progressão da doença em indivíduos infectados pelo HIV 54,55 . O receptor de membrana CD95 está envolvido na morte acelerada de linfócitos T no contexto de infecção pelo HIV, através da indução de apoptose, e é considerado marcador de exaustão e ativação celular [56][57][58][59] .…”
Section: Impacto Da Tarv Nos Desfechos De Saúde Na Criança Ativação unclassified